Addressing Residency Work Hours: An Introduction to the American System of Night Float - Starkey, Jay; Teo, Alan R. (Igaku Kyoiku / Medical Education (Japan), 2011)
1)In the aftermath of a well-known case of medical malpractice in the U.S., excessive resident work hours became a major national issue. In order to help reduce resident work hours, the system of night float was developed. 2)In the night float system, the resident on duty has no daytime clinical responsibilities and instead works solely on the night shift. Typically, residents have multiple night float rotations, lasting one to two weeks each, over the course of a year. 3)In medical centers where night float is utilized, residents who are not on night float are relieved of responsibility for providing overnight clinical coverage of their patients. Resident satisfaction with this system has been high, and the night float has been adopted by residency training programs throughout the U.S. 4)The night float system has benefits not only in terms of reducing resident work hours but also potentially improving certain clinical skills, promoting patient safety, and enhancing other areas. However, some studies have shown drawbacks of the system in the areas that other studies have hailed improvements.